Kekuatan Monitoring Internal Dan Eksternal, Biaya Keagenan Serta Dampaknya Terhadap Kebijakan Deviden - Lailah Fujianti (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
Some of the results of previous studies related to agency costs and dividend policy found any contradictory results, so that the study was designed as a development of previous research that aims to determine how the influence of internal and external monitoring of the agency costs, and how the influence of these variables on dividend policy. Object of the study is a company registered in the Indonesia Stock Exchange in 2011. The sampling method was purposive sampling is included in the list of 45 companies that make up the LQ and does not include financial institutions as well as share dividend. Total sample used 38 companies. The method of analysis is the Partial Least Square (PLS). The results showed internal and external monitoring variables significantly influence agency costs. Internal monitoring variables affect the dividend policy while monitoring external variables and agency costs are not significant.